Regulatory Functions of Natural Killer Cells in Multiple Sclerosis - Gross, Catharina C.; Schulte-Mecklenbeck, Andreas; Wiendl, Heinz; Marcenaro, Emanuela; Kerlero de Rosbo, Nicole; Uccelli, Antonio; Laroni, Alice (Frontiers in Immunology, 2016)
There is increasing evidence that natural killer (NK) cells exhibit regulatory features. Among them, CD56bright natural killer cells have been suggested to play a major role in controlling T-cell responses and maintaining homeostasis. Dysfunction in NK cell-mediated regulatory features has been recently described in untreated multiple sclerosis (MS), suggesting a contribution to MS pathogenesis. Moreover, biological disease-modifying treatments effective in MS apparently enhance the frequencies and/or regulatory function of NK cells, further pointing toward an immuno-protective role of NK cells in MS. Here we summarize the current knowledge on the regulatory functions of NK cells, based on their interactions with other cells belonging to the innate compartment, as well as with adaptive effector cells. We review the more recent data reporting disruption of NK-cell/T-cell interactions in MS, and discuss how disease-modifying treatments for MS affect NK cells.